2020
DOI: 10.5897/jaerd2020.11322
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adoption of agricultural extension package technologies by smallholder households on sorghum production: Case of Gemechis and Mieso districts of West Hararghe Zone, Oromia Regional State, Ethiopia

Abstract: This study identified the socio-economic factors that significantly influence adoption of agricultural extension package technologies on sorghum crop production. Primary and secondary data were collected for the study. In the sampling procedure, multi stage sampling procedure was used. Data was analyzed using both descriptive statistics and econometric models. In econometric models Multivariate Probit (MVP) and Double Hurdle models were used. Multivariate Probit output indicates that, the probability of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The similarities among the three regions in terms of reasons for abandonment are; introduction of better varieties, long duration varieties, lost of varieties during the war, low root yield and poor planting materials. These report is inconsistent with results shown by [26] and that provisions of inputs, knowledge and technical skills provided by policy makers helped in the not abandonment of varieties.…”
Section: Similarities Of Reasons Across Regioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The similarities among the three regions in terms of reasons for abandonment are; introduction of better varieties, long duration varieties, lost of varieties during the war, low root yield and poor planting materials. These report is inconsistent with results shown by [26] and that provisions of inputs, knowledge and technical skills provided by policy makers helped in the not abandonment of varieties.…”
Section: Similarities Of Reasons Across Regioncontrasting
confidence: 69%
“…Additionally, the highest consumption of cassava leaves per day was recorded in the northern region compared with the eastern and southern regions. It had been previously reported that leaves of cassava are used as a vegetable where they provide significant proportion of protein and other nutrients [26] [27] [28].…”
Section: Utilization Of Leaves As Foodmentioning
confidence: 99%
“…Ecological cognition reflects the extent of an individual's knowledge of ecology. It is a mental understanding formed by an individual's continuous accumulation of relevant and ecological environmental knowledge through acquisition, understanding, and learning [31]. According to the theory of planned behavior, under the conditions of uncertainty, behavioral attitudes, subjective norms, and perceived behavioral control jointly influence behavior, while other factors indirectly influence individual behavioral decisions through these three.…”
Section: Hypothesis 1 Acceptance Of Agricultural Extension Services C...mentioning
confidence: 99%